Differential Protein-Coding Gene Expression Profile in Patients with Prostate Cancer - Lorena Albarracín-Navas; Maylin Almonte-Becerril; Enmanuel Guerrero; Josue Rivadeneira; Marcelino Telechea-Fernández; Elizabeth Guzmán; Fanny Calderón; María José Hernández-Leal; Tamara Otzen; Carlos Manterola; Galo Duque; Ángela L. Riffo-Campos (Biomedicines, 2024)
Background: Prostate cancer is the second most common neoplasm in men, with projections estimating over one million new cases by 2045. Differentially expressed genes can significantly enhance the diagnosis, treatment, monitoring, and prognosis of this disease. Purpose: to systematically review and analyze validated differentially expressed mRNAs in prostate cancer patients to propose a robust molecular profile for clinical diagnostics. Methods: A systematic review was conducted following PRISMA guidelines, searching literature databases for mRNAs with validated differential expression in adult prostate cancer patients. Identified mRNAs were analyzed using STRING, Cytoscape, and DrugBank to explore protein–protein interactions and potential drug targets. Results: A total of 5003 participants from Europe, Asia, America, and Oceania were included, and 144 mRNAs (p < 0.05) were reported across 75 primary articles, predominantly validated using RT-qPCR with tissue samples. Among these, at least 36 mRNAs were identified as targets for cancer-related drugs. Enrichment analysis revealed the top pathways were associated with cancer, including specific prostate cancer terms. Key nodes emerged as hubs in the protein–protein interaction network. Conclusion: Based on our comprehensive in silico analysis of validated differentially expressed mRNAs, we propose a molecular profile of twenty-five mRNAs with significant potential for clinical diagnosis of prostate cancer. These findings offer a valuable foundation for developing precision oncology strategies to improve patient outcomes.